2019
DOI: 10.1108/aeat-01-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement of helicopter rotors through blade redesigning

Abstract: Purpose The purpose of this paper is to determine dependencies between a rotor-blade shape and a rotor performance as well as to search for optimal shapes of blades dedicated for helicopter main and tail rotors. Design/methodology/approach The research is conducted based on computational methodology, using the parametric-design approach. The developed parametric model takes into account several typical blade-shape parameters. The rotor aerodynamic characteristics are evaluated using the unsteady Reynolds-ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Bu yaklaşımda yatay kuyruk helikopter uzunlamasına eksenine göre kolektif ve diferansiyel sapmalar yapmakla beraber, helikopter uzunlamasına ekseninde ileri/geri hareketlerde gerçekleştirebilmektedir (bknz. Sherry, 1953;Stuart, 1961;Howlett, 1981;Bluman ve Gandhi, 2011;Oktay ve Şal, 2015;Oktay ve Sultan, 2013a). Bir diğer tasarım yaklaşımı helikopter ana rotor palelerinin bazı özelliklerini yeniden tasarlamaktır.…”
Section: Introductionunclassified
“…Bu yaklaşımda yatay kuyruk helikopter uzunlamasına eksenine göre kolektif ve diferansiyel sapmalar yapmakla beraber, helikopter uzunlamasına ekseninde ileri/geri hareketlerde gerçekleştirebilmektedir (bknz. Sherry, 1953;Stuart, 1961;Howlett, 1981;Bluman ve Gandhi, 2011;Oktay ve Şal, 2015;Oktay ve Sultan, 2013a). Bir diğer tasarım yaklaşımı helikopter ana rotor palelerinin bazı özelliklerini yeniden tasarlamaktır.…”
Section: Introductionunclassified
“…As an output, a geometry generator is prepared with initial optimization functions. Other main rotor optimization studies with focusing on aerodynamic optimization were presented in (Stalewski, 2017a,b;Xie et al, 2017;Stalewski and Zalewski, 2019;Okumuş et al, 2022) while optimization procedure for best flight performance was shown in (Slavik et al, 2029).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the study by Oktay and Sultan (2014) active morphing was very useful, and the active morphing parameters were blade radius, chord length, angular speed and twist. Using this novel approach approximately 85% of the control effort throughout 80 kts SLF condition (visit also other articles such as Ganguli, 2002; Fusato and Celi, 2006; Hodges et al , 2008; Kang et al , 2010; Barbarino, 2011; Vu et al , 2013; Kambampati and Ganguli, 2016; Stalewski and Zalewski, 2019; Shahmiri et al , 2019; and Sal, 2020 for different redesign applications) was saved.…”
Section: Introductionmentioning
confidence: 99%